Ḍākṭar Vazīr Āġ̱ā kī inšāʾiyah nigārī kā tanqīdī mut̤ālʿah - Quraišī, Muḥammad Yūsuf (Taẖlīqkār Pablišarz, 2010)
On the works of Vazīr Āg̱ẖā, 1922-, eminent Urdu writer
Originally presented as the author's thesis. - In arab. Schrift, Urdu. - Title on t.p. verso in roman: Dr. Wazir Agha ki inshaiya nigari ka tanqeedi mutalea
Keywords: Hochschulschrift; Vazīr Āg̱ẖā 1922-